HAK ULAYAT SUKU PAGU DAN PENGAKUAN HUKUM PEMERINTAH (STUDI DI KECAMATAN KAO HALMAHERA UTARA) - Nolfan Hibata; Reli Jevon Laike (Penerbit Universitas Atma Jaya Yogyakarta, 2020)
The implementation of the recognition of indigenous legal rights always raises issues such as the civility of ulayat rights and the implementation of recognition by the state. This is as well as the rights of the Pagu tribe. The purpose of this research is to examine the existence of the rights of the ulayat tribe and the problem has not been recognized by the government. This study uses normative research with its main focus on the right of ulayat from the legal aspects and recognition of local governments to be analyzed based on the results of the study of primary legal materials to come to a conclusion. The results of the study found that the existence or existence of pagu ulayat rights still exists, but leaves some problems among them until this saaat the government has not recognized its customary territory which has an impact on the neglect of the rights contained in it. Second, the rights of the Pagu tribe have not been recognized by the local government on the other side of the pagu institution has been recognized, this then leaves a complicated and prolonged problem, where the Pagu tribe does not get protection and legal certainty, thus ignoring the rights to use, seek and collect the results that exist within its customary territory. It should be recognized by the institution of the Pagu tribe by itself has been covered by the rights of ulayat in it.